2021
DOI: 10.1021/acs.est.1c02853
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of Highly Stable Pt Single Sites on Defect Engineered Ceria into Robust Pt Clusters for Vehicle Emission Control

Abstract: Engineering surface defects on metal oxide supports could help promote the dispersion of active sites and catalytic performance of supported catalysts. Herein, a strategy of ZrO 2 doping was proposed to create rich surface defects on CeO 2 (CZO) and, with these defects, to improve Pt dispersion and enhance its affinity as single sites to the CZO support (Pt/CZO). The strongly anchored Pt single sites on CZO support were initially not efficient for catalytic oxidation of CO/C 3 H 6 . However, after a simple act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 68 publications
2
36
0
Order By: Relevance
“…H 2 -TPR technique is a powerful tool to evaluate the dispersion of Pt species as well as the strength of Pt-O-Ce interaction on Pt/CeO 2 based catalysts 39 , 40 . Herein, the H 2 -TPR profiles of Pt/CeO 2 -550, Pt/CeO 2 -700, Pt/CeO 2 -800 were collected to investigate the interaction between Pt single atoms and CeO 2 support (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…H 2 -TPR technique is a powerful tool to evaluate the dispersion of Pt species as well as the strength of Pt-O-Ce interaction on Pt/CeO 2 based catalysts 39 , 40 . Herein, the H 2 -TPR profiles of Pt/CeO 2 -550, Pt/CeO 2 -700, Pt/CeO 2 -800 were collected to investigate the interaction between Pt single atoms and CeO 2 support (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Liu et al prepared a zirconium-doped CeO 2 (CZO) catalyst rich in oxygen defects by doping zirconium into the lattice of CeO 2 and proved the existence of abundant oxygen vacancies on the surface of the CZO support using this characterization method. 100…”
Section: In Situ Diffuse Reectance Infrared Fourier Transformed Spec...mentioning
confidence: 99%
“…9D, Liu et al used abundant surface defects in zirconium-doped CeO 2 (CZO) carriers to anchor Pt, which improved the dispersion of Pt and made it outstanding in propylene oxidation. 100 He et al found that the oxygen vacancies of CeO 2 could stabilize Pt atoms and proposed that the stabilization mechanism relied on the distortion of the Pt-O-Ce interface formed by the strong metal-carrier interaction to maintain thermodynamic stability. 37 In addition, many studies have accepted oxygen vacancies as Lewis acid sites to compensate for the acidity of catalysts.…”
Section: Anchoring and Lewis Acid Sitesmentioning
confidence: 99%
“…The generation of asymmetric oxygen vacancies and their boosted catalytic oxidation activity have been demonstrated on various redox reaction systems. 17−21 The oxygen vacancies on oxides can act as trapping and stabilizing centers for metal atoms and clusters, 22 generating asymmetric interfacial oxygen vacancy sites 23,24 and promoting charge transfer between metal and oxide substrates. 25 It was reported that Pt atoms could be stabilized on oxygen vacancies of CeO 2 through a spontaneous interfacial distortion to form Pt−O−Ce interfacial sites, which were advantageous to the adsorption and activation of O 2 and methanol.…”
Section: Introductionmentioning
confidence: 99%